Muslim insurgency, political violence, and democracy in Thailand - Croissant, Aurel (Terrorism and political violence, 2007)
In the past couple of years, Thailand's three southernmost provinces have become a hotspot of ethnic insurgency. This article analyzes the insurgency from two perspectives. The first relates to the causes, contours, and involved groups of the conflict. The analysis will show that the roots of radicalism can be traced to several contentious religious, cultural, economic, and political causes such as cultural discrimination, relative economic deprivation, and political alienation. However, the drift toward militancy in the past years is mainly caused by recent shifts in the local and regional political environment of Thailand's deep South. The second perspective relates to the political consequences of the unrest. While it is highly unlikely that extremists will reach their separatist goal, insurgency and counter-insurgency contribute to the erosion of liberal democracy in Thailand. Immediate consequences of (counter)-insurgency such as the erosion of respect for human rights and other political rights and the deepening political divide in Thai society contribute to the emergence of an illiberal or semi-democratic political regime, characterized by the rise of a single political party and its all-powerful political leader to near-hegemonic power.
Gesehen am 25.03.2021